Meningkatkan Kemampuan Motorik Halus Melalui Teknik Mozaik Menggunakan Bahan Alam Pada Anak Usia 5-6 Tahun - Musripa, Musripa; Sabani, Fatmaridah; Subhan; Bulu', Rifa’ah Mahmudah; Hutami, Eka Poppi (YAYASAN YASZOY CAYAHA NUSANTARA, 2024)
This research aims to determine how to improve the fine motor skills of children aged 5-6 years at TKIT Waladun Shalih. The type of research used is classroom action research, with two cycles, namely cycle I consisting of 4 meetings and cycle II consisting of 4 meetings. The subjects of this research were teachers and children aged 5-6 years at TKIT Waladun Shalih, consisting of 2 teachers and 16 children consisting of 10 boys and 6 girls. The problem solving method used in the teaching and learning process in offline learning is the mosaic technique using natural materials, using interview research instruments, observation and documentation. The data analysis technique was carried out descriptively quantitatively. The research results show that there is an increase in fine motor skills. The improvement in fine motor skills can be seen based on scores in the initial or pre-action conditions with 11 children in the not yet developing category, and 5 children in the beginning to develop category. Then in the first cycle there was an increase with 5 children in the not yet developing category, then in the starting to develop category there were 7 children, and in the developing according to expectations category there were 4 children. And the increase that occurred in cycle II with the category developing according to expectations was 6 children, and in the very well developing category there were 10 children. The success of this research is determined by the child's score which shows that the child's learning outcomes have improved.